A 'uses and gratification expectancy model' to predict students' 'Perceived e-Learning Experience' - Makingu, Mondi; Peter, Woods; Ahmad, Rafi (IEEE COMPUTER SOC, 2008)
This study investigates 'how and why' students' 'Uses and Gratification Expectancy' (UGE) for e-learning resources influences their 'Perceived e-Learning Experience.' A 'Uses and Gratification Expectancy Model' (UGEM) framework is proposed to predict students' 'Perceived e-Learning Experience,' and their uses and gratifications for electronic media in a blended learning strategy. The study utilises a cross-sectional research design, and elicits data from secondary school students through a field survey-questionnaire. The findings suggest that there are significant relationships between five dimensions of students' UGE for e-learning resources, and their 'Perceived e-Learning Experience.' It is plausible that these UGE aspects of students' 'communication behaviour' towards electronic media are important determinants of effective integration of the e-learning resources in school-curriculum. While this research focuses on students at secondary-school level, some elements in the UGE model may apply to students using e-learning resources at other levels of their education. This model gives researchers and educators a new tool to forecast the success of development and deployment of e-learning resources in education systems.